Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write Dilengkapi Time Token Terhadap Kompetensi Fisika Kelas X - Imron Maulana; Hidayati Hidayati; Ramli Ramli (PILLAR OF PHYSICS EDUCATION, 2018)
This investigation is support on the number of students who are less active in physics learning. Learners tend to be less courageous to ask questions and express their opinions on learning, thus causing the physics competence of learners to be lower than the minimum limit set by the school. The use of cooperative learning model is rarely. Also still limited teaching materials to help learners on learning. The functional of study to investigate the effect of applying the learner sheet in the model of cooperative learning type Think Talk Write completed with a time token to the physics competence of students of class X MIA SMAN 14 Padang. The type of research conducted is Quasi Experiment Research. Sampling is done by Purposive Sampling technique. Research instruments include knowledge competence test, attitude and skill competence observation sheet. From the data case study can be expressed the results of this investigation, there is a significant difference of competence between learners using the learner's Worksheet in the cooperative learning model of type talk talk write completed time token with learners who do not use, Furthermore the influence of student worksheet application in cooperative learning model type think talk write has a meaningful time token against the competence of students of class X MIA SMAN 14 Padang at the real level of 0.05.